Fracture strength testing of crowns made of CAD/CAM composite resins. Issue 3 (July 2018) - Okada, Ryota; Asakura, Masaki; Ando, Akihiro; Kumano, Hirokazu; Ban, Seiji; Kawai, Tatsushi; Takebe, Jun
Abstract: Purpose: The purpose of this study was to ascertain whether computer aided design/computer aided manufacturing (CAD/CAM) composite resin crowns have sufficient strength to withstand the bite force of the molar teeth. The null hypothesis was that the fracture strength of CAD/CAM composite resin crowns is lower than the average maximum bite force of the molar tooth. Methods: The crowns, which shape is the right maxillary first molar, were fabricated using four CAD/CAM blanks made of composite resins (Block HC: HC, KZR-CAD HR: HR, KZR-CAD HR2: HR2, Avencia Block: AVE) and one CAD/CAM blank made of lithium disilicate glass-ceramic (IPS e.max CAD: IPS), which was used as a control. Fracture strength of fabricated crowns bonded to metal abutment and biaxial flexural strength of the materials were evaluated. Results: The results of fracture strength test and biaxial flexural strength test showed different tendencies. The fracture strength of CAD/CAM composite resin crowns except HC ranged from 3.3 kN to 3.9 kN, and was similar to that of IPS (3.3 kN). In contrast, biaxial flexural strength of CAD/CAM composite resins ranged from 175 MPa to 247 MPa, and was significantly lower than that of IPS (360 MPa). Conclusions: All CAD/CAM composite resin crowns studied presented about 3–4 times higher fracture strength than the average maximum bite force of the molar tooth (700–900 N), which result leads to the conclusion that CAD/CAM composite resin crowns would have sufficient strength to withstand the bite force of the molar teeth.